Newly Found Simile in Persian Literature; Negative and Positive Simile - saeed karimi qare baba (مطالعات زبانی و بلاغی)
In this article a distinctive simile in rhetoric is represented as negative and positive simile neglected by rhetoric scholar until now, while it has been influential in the formation of figures of speech. In negative and positive simile, a poet first rejects similarity of a topic to someone or something, and then immediately proves the similarity of the same topic to someone or something in the opposing point of the previous image. Author of the present article has described the quality of the type of simile relying on a number of instances in Persian literature. The oldest case of such simile is seen in an ode penned by Naser Khosrow. The aim of negative and positive simile, like any other simile, is describing a topic or exaggerating on it, but these rhetoric intentions are achieved through novel ways. By providing a kind of contrast and distinction between two images, a poet focuses on their similarity leading to stronger impression and sentiment. Such contrast gives a pictorial basis of meaning. In addition, employing negative and positive simile, poets establish connections between dissimilar individual and entities and make their readers surprised.